ИСПОЛЬЗОВАНИЕ ЭКОЛОГИЧЕСКИХ БЕЗВРЕДНЫХ СТИМУЛЯТОРОВ И ЗАЩИТНЫХ СРЕДСТВ ДЛЯ КАПСУЛИРОВАНИЯ СЕМЯН РАПСА (Experimental biology, 2015)
The paper discusses the component composition for pelleting seed crops are their own results of laboratory testing of rapeseed (Brassica napus L.), subjected to the encapsulation. Were given the characteristics of the seed drops, defined germination and seed vigor.
Keywords: composition; seed vigor